Supramacroparticulate PE in 6 different joint endoprostheses localisations: An indicator for PE damage? - Krenn, Simon; Kretzer, Jan Philippe (Pathology, research and practice, 2017)
In the histopathological particle algorithm polyethylene (PE) particles with maximum lengths of more than 100μm - called PE supramacroparticles - are identified exclusively for knee joint and hip prostheses. However, a definitive characterisation, detection in all joint localisations and a causal clarification of the pathogenesis are lacking. In this study a total of 175 SLIM (synovial-like interface membrane) cases with PE supramacroparticles of knee joint prostheses (n=89), hip joint prostheses (n=44), ankle joint prostheses (n=36) and prostheses in three localisations of the upper extremities (n=6) were systematically investigated. The arithmetic mean of the particle length varied greatly within the prosthesis types. This had a significant positive correlation with the prosthesis lifetime and negative correlation with the date of implantation. It can be concluded that both the lifetime and the time of implantation have an influence on the particle length. The prostheses with supramacroparticulate damage moreover showed a clearly reduced survival rate compared with other data published on the prosthesis lifetime. The material wear therefore could not be attributed solely to the usual fatigue factors. Since loosening of the prostheses, decentring of the PE components or damage to the PE inlay existed in all cases, mechanical dysloading seems to be the most probable cause of PE supramacroparticle genesis. Due to the striking length and for demarcation from PE macroparticles, the term supramacroparticulate PE is proposed for a length of more than 100μm. In the extended histopathological particle algorithm supramacroparticulate PE has been included in the macroparticles category and should be taken into account and interpreted causally in histopathological diagnostics of joint prosthesis failure.